2021
DOI: 10.1183/23120541.00255-2021
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of single-inhaler triple therapy of glycopyrronium, formoterol and fluticasone in patients with COPD: a double-blind, randomised controlled trial

Abstract: BackgroundInvestigating the safety and efficacy of single-inhaler triple therapy with glycopyrronium (GB) 12.5 μg/formoterol fumarate (FF) 12 μg/fluticasone propionate (FP) 250 μg, compared to GB 50 μg co-administered with a fixed dose of FF 12 μg/FP 250 μg in subjects with COPD.MethodsA phase 3, randomised, double-blind, active-control, parallel-group, noninferiority study conducted at 20 sites across India. COPD patients aged ≥40 to ≤75 years, with FEV1/FVC <0.70, using mono/dual therapy with ICS, LAMA, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, for patients predisposed towards poor adherence, single-inhaler triple therapy could be considered. A recent study showed that bronchodilation and lung-function improvement was comparable in the single-inhaler triple therapy and open triple therapy [ 59 ]. Box 8 represents expert panel recommendations on the use of triple therapy in COPD.…”
Section: Resultsmentioning
confidence: 99%
“…However, for patients predisposed towards poor adherence, single-inhaler triple therapy could be considered. A recent study showed that bronchodilation and lung-function improvement was comparable in the single-inhaler triple therapy and open triple therapy [ 59 ]. Box 8 represents expert panel recommendations on the use of triple therapy in COPD.…”
Section: Resultsmentioning
confidence: 99%
“… 4 , 32 Two previous randomized trials showed comparable efficacy of SITT and MITT in reducing the risk of exacerbations. 33 , 34 A recent Delphi study by Lopez-Campos et al also noted the agreement on triple therapy resulting in improvement in lung function and reduction in exacerbation risk in patients with COPD. 35 A consensus was reached in the current Delphi study regarding triple therapy being more beneficial compared to dual therapy in frequent exacerbators and with SITT being considered more effective than MITT in reducing exacerbations.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, in addition to these triple combinations already on the market, there are at least two more in process of development. On the one hand, the combination of Fluticasone propionate with formoterol and glycopyrronium has recently been published after its first phase 3 trial in India 27 . It is administered in a pMDI every 12 hours and shows similar efficacy to open-label triple therapy.…”
Section: Single-inhaler Triple Therapies For Copdmentioning
confidence: 99%